Fatty acid desaturase activity in mature red blood cells and implications for blood storage quality. Issue 6 (26th April 2021) - Thomas, Tiffany; Cendali, Francesca; Fu, Xiaoyun; Gamboni, Fabia; Morrison, Evan J.; Beirne, Jonathan; Nemkov, Travis; Antonelou, Marianna H.; Kriebardis, Anastasios; Welsby, Ian; Hay, Ariel; Dziewulska, Karolina H.; et al.
Abstract: Background: Increases in the red blood cell (RBC) degree of fatty acid desaturation are reported in response to exercise, aging, or diseases associated with systemic oxidant stress. However, no studies have focused on the presence and activity of fatty acid desaturases (FADS) in the mature RBC. Study design and methods: Steady state metabolomics and isotope‐labeled tracing experiments, immunofluorescence approaches, and pharmacological interventions were used to determine the degree of fatty acid unsaturation, FADS activity as a function of storage, oxidant stress, and G6PD deficiency in human and mouse RBCs. Results: In 250 blood units from the REDS III RBC Omics recalled donor population, we report a storage‐dependent accumulation of free mono‐, poly‐(PUFAs), and highly unsaturated fatty acids (HUFAs), which occur at a faster rate than saturated fatty acid accumulation. Through a combination of immunofluorescence, pharmacological inhibition, tracing experiments with stable isotope‐labeled fatty acids, and oxidant challenge with hydrogen peroxide, we demonstrate the presence and redox‐sensitive activity of FADS2, FADS1, and FADS5 in the mature RBC. Increases in PUFAs and HUFAs in human and mouse RBCs correlate negatively with storage hemolysis and positively with posttransfusion recovery. Inhibition of these enzymes decreases accumulation of free PUFAs and HUFAs in stored RBCs, concomitant to increases in pyruvate/lactate ratios. Alterations of this ratio in G6PD deficient patients or units supplemented with pyruvate‐rich rejuvenation solutions corresponded to decreased PUFA and HUFA accumulation. Conclusion: Fatty acid desaturases are present and active in mature RBCs. Their activity is sensitive to oxidant stress, storage duration, and alterations of the pyruvate/lactate ratio.